Is Happiness Good for Your Personality? Concurrent and Prospective Relations of the Big Five With Subjective Well-Being - Soto, Christopher (My University, 2014)
The present research examined longitudinal relations of the Big Five personality traits with three core aspects of subjective well-being: life satisfaction, positive affect, and negative affect. Latent growth models and autoregressive models were used to analyze data from a large, nationally representative sample of 16,367 Australian residents. Concurrent and change correlations indicated that higher levels of subjective well-being were associated with higher levels of Extraversion, Agreeableness, and Conscientiousness, and with lower levels of Neuroticism. Moreover, personality traits prospectively predicted change in well-being, and well-being levels prospectively predicted personality change. Specifically, prospective trait effects indicated that individuals who were initially extraverted, agreeable, conscientious, and emotionally stable subsequently increased in well-being. Prospective well-being effects indicated that individuals with high initial levels of well-being subsequently became more agreeable, conscientious, emotionally stable, and introverted. These findings challenge the common assumption that associations of personality traits with subjective well-being are entirely, or almost entirely, due to trait influences on well-being. They support the alternative hypothesis that personality traits and well-being aspects reciprocally influence each other over time.
Keywords: Health -- Wellbeing; Satisfaction -- Life; Beliefs and Values -- Personality; Identity; Health and wellbeing; Health; Beliefs and Values; Satisfaction; Wellbeing; Personality; Life; Health and wellbeing; Identity